Mammalian Models of Traumatic Brain Injury and a Place for Drosophila in TBI Research - Shah, Ekta J.; Gurdziel, Katherine; Ruden, Douglas M. (Frontiers in Neuroscience, 2019)
Traumatic brain injury (TBI), caused by a sudden blow or jolt to the brain that disrupts normal function, is an emerging health epidemic with ∼2.5 million cases occurring annually in the United States that are severe enough to cause hospitalization or death. Most common causes of TBI include contact sports, vehicle crashes and domestic violence or war injuries. Injury to the central nervous system is one of the most consistent candidates for initiating the molecular and cellular cascades that result in Alzheimer’s disease (AD), Parkinson’s disease (PD) and amyotrophic lateral sclerosis (ALS). Not every TBI event is alike with effects varying from person to person. The majority of people recover from mild TBI within a short period of time, but repeated incidents can have deleterious long-lasting effects which depend on factors such as the number of TBIs sustained, time till medical attention, age, gender and genetics of the individual. Despite extensive research, many questions still remain regarding diagnosis, treatment, and prevention of long-term effects from TBI as well as recovery of brain function. In this review, we present an overview of TBI pathology, discuss mammalian models for TBI and focus on current methods using Drosophila melanogaster as a model for TBI study. The relatively small brain size (∼100,000 neurons and glia), conserved neurotransmitter signaling mechanisms and sophisticated genetics of Drosophila allows for cell biological, molecular and genetic analyses that are impractical in mammalian models of TBI.